Public Policy and Teacher Education in STS - Isabel P., (Uni-pluriversidad, 2014)
Education and training are interrelated concepts which are appropriated by all public policies frequently with distinct meanings. In this context, education is perceived as a goal and training as a process that will lead to that purpose. We are dealing with STS education within a context of formal scientific education and with guidelines to teacher education that may reach that purpose, assuming that there is a wide range of concepts concerning STS education. We present guidelines to science education in a broad international panorama and teacher training perspectives adopted by political power, according to the conveyed perspectives on education, school and learning. We analyse curricular guidelines concerning science teaching and legislation concerning teacher training both in Portugal and Spain. Within the framework of science education oriented towards STS/STSE/ESD, empirical documentary data were collected in eleven Portuguese institutions of teacher training from basic to secondary schooling, aiming at characterising ongoing teacher training perspectives. The analysis of the curricular unit’s programmes allowed verifying that they present explicit evidences on the subject both on initial and continuous teacher training. Although initial teacher training is not the only determinant factor of education quality, it is fundamental and it should continue in continuous education. Higher Education Institutions in Portugal have qualified teachers who develops research on STS | ESD education which is crucial to outline effective policies on science teachers’ training.